Longitudinal study of risk factors for anaplasmosis and transplacental transmission in herd cattle - Da Silva, Jenevaldo Barbosa [UNESP]; De SantanaCastro, Gustavo Nunes; Fonseca, Adivaldo Henrique (Universidade Estadual de Londrina, 2014)
Anaplasma marginale, bacteria that occurs in tropical and subtropical areas throughout the world, is responsible for causing a disease that is one of the most constraint to cattle production in many countries. The present work aimed to investigate potential risk factors for anaplasmosis and the occurrence of transplacental transmission by molecular and serological assays in cattle. A total of 22 calves were randomly sampled and monitored during four years; the presence of infection/exposure to A. marginale was assessed by a semi-nested PCR assay targeting msp-5 gene of A. marginale, indirect ELISA for detection of IgG antibodies to A. marginale and blood smears. The A. marginale infection prevalence data were analyzed in relation to risk factors, using chi-squared, odds ratio and multiple logistic regressions. DNA amplification results revealed a frequency of infection with A. marginale of 41% (9/22) in the newborn calves before colostrum suckling. However, only 14% (3/22) of newborn calves were seropositive for A. marginale. All calves were positive to A. marginale by PCR and microscopic examination of blood smears before the two and fourth month of age, respectively. The main risk factors associated with seroprevalence were breed (OR=36.2), tick infestation (OR=3.44) and stocking density (OR=3.28). The results indicated that exposure of cattle to A. marginale was common in dairy herds and endemic instability situation probably is due to inadequate antibody production in cows or genetic variability of pathogen. This study still demonstrated that in addition to transmission of A. marginale by ticks and flies, the transplacental transmission is very important and should be the target of disease control programs in Brazil.
Keywords: Anaplasma marginale; Blood smear; ELISA; PCR